2014
DOI: 10.1186/s12913-014-0485-5
|View full text |Cite
|
Sign up to set email alerts
|

Creating advantages through franchising in healthcare: a qualitative, multiple embedded case study on the role of the business format

Abstract: BackgroundBusiness format franchising is an organizational form that originates from the business sector. It is increasingly used in healthcare, being a promising organizational form for improving the competitiveness and efficiency of organizations, the quality of care, and the professional work environment. However, evidence is lacking concerning how these healthcare franchises should be designed to actually deliver the promised benefits. This study explores how the design of the central element in franchisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This research used a qualitative, embedded, multiple case study design whose value has been demonstrated in previous health services research (eg, [32][33][34]). Researchers from the three health services collaborated with university researchers who were independent from those health services to initiate the project (project-managed by researcher URK), and gather and analyze data from people who had been involved in either clinical or technical aspects of designing and deploying the virtual care tools that were the focus of study: Austin Health community self-assessment platform [35], Austin Health COVID-19 symptom monitoring system, Austin Health COVID-19 symptoms management tool, Bendigo Health teamplay myCare Companion "Pandemic" [36,37], Royal Melbourne Hospital Home Monitoring [22,38], Royal Melbourne Hospital Screening Clinic tool, and Royal Melbourne Hospital COVIDCare.…”
Section: Designmentioning
confidence: 99%
“…This research used a qualitative, embedded, multiple case study design whose value has been demonstrated in previous health services research (eg, [32][33][34]). Researchers from the three health services collaborated with university researchers who were independent from those health services to initiate the project (project-managed by researcher URK), and gather and analyze data from people who had been involved in either clinical or technical aspects of designing and deploying the virtual care tools that were the focus of study: Austin Health community self-assessment platform [35], Austin Health COVID-19 symptom monitoring system, Austin Health COVID-19 symptoms management tool, Bendigo Health teamplay myCare Companion "Pandemic" [36,37], Royal Melbourne Hospital Home Monitoring [22,38], Royal Melbourne Hospital Screening Clinic tool, and Royal Melbourne Hospital COVIDCare.…”
Section: Designmentioning
confidence: 99%
“…Franchising has been traditionally linked to food service (Lewandowska 2014). Recent studies have looked at the design elements in business format franchising (e.g., brand name, support systems, specification of products and services), and link these elements to performance (Nijmeijer et al 2014).…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…Researchers have investigated knowledge management in franchise networks (see review by Iddy & Alon, 2019), but little is known yet on how knowledge is transferred in developing economies (Khan, 2016;Perrigot et al, 2017). Following the call by (Nijmeijer, Huijsman, & Fabbricotti, 2014) to investigate knowledge transfer mechanisms in franchising, this study seeks to answer the question: How is knowledge transferred within franchise networks in emerging markets?…”
Section: Introductionmentioning
confidence: 99%